WAKTU PELEPASAN TALI PUSAT PADA NEONATUS LEBIH CEPAT DENGAN PENERAPAN METODE TERBUKA - Yuni Lestariningsih; Fida' Husain (Journal Keperawatan, 2022)
Neonatal tetanus infection and umbilical cord infection (omphalitis) are the main causes of morbidity and mortality in infants throughout the country, especially in Southeast Asia due to improper umbilical cord care. Umbilical cord care is carried out after the neonate is born until the umbilical cord is released with great care, attention and care to prevent infection in the umbilical cord. The purpose of this study was to describe the results of implementing the implementation of umbilical cord care with the open method in neonates. This type of research method uses a case study by applying the open method of umbilical cord care to determine the timing of the release of the umbilical cord. The results of the condition of the neonate's umbilical cord Ny. A and Mrs. T has not been released, before the umbilical cord is treated with an open method. While the condition of the neonate's umbilical cord, Ny. A and Mrs. T has been released, after the open method of umbilical cord treatment with the release of the umbilical cord in the neonate Ny. A was released on the 4th day, quickly (umbilical cord detachment time <5 days) and the neonate Mrs. T loose on day 5, normal (time of umbilical cord detachment 5-7 days). Based on the results of the final evaluation, there are differences in the development of the umbilical cord release time before and after being given the open method of umbilical cord care.